Genetic Characterization of Corynebacterium pseudotuberculosis Isolates in Egypt - Nadine A. El-Sebay (Egyptian Society for Animal Management, 2021)
Corynebacterium pseudotuberculosis is a small Gram-positive bacillus containing mycolic acid in the structure of the cell wall. The bacterium is responsible for Caseous Lymphadenitis (CLA) in small ruminants (sheep and goats). The bacteria are also responsible for Ulcerative Lymphangitis in equines. The disease causes great economic loss in the animal industry. This work aimed to check the ability of Quadruplex PCR (Q-PCR) for genotyping and identification of Egyptian isolates of C. pseudotuberculosis and sequence analysis of phospholipase D (PLD) gene of local isolates. Four of C. pseudotuberculosis local isolates previously biochemically identified were tested for narG gene (nitrate reductase gene). Both nitrate negative biovar (ovis) and nitrate positive biovar (equi) showed a positive result for 16S rRNA, rpoB and PLD genes of C. pseudotuberculosis species. The sequence analysis of our local isolates' PLD gene revealed minor changes in PLD proteins between ovine and equine strains compared with other published PLD sequences in GenBank. It was concluded that the Q-PCR method is able to differentiate between C. pseudotuberculosis equi and ovis biovars. Also, the sequence of PLD gene of local isolates representing the two biovars revealed some variation, which leads to an accurate diagnosis of C. pseudotuberculosis biovars and generates a mapping of immerged local isolates. Further, the PCR and sequence of these isolates provide rapid and accurate genotyping, especially with hyperimmune serum's unavailability.